KERJA SAMA INDONESIA DAN UNICEF DALAM MENGATASI MASALAH AIR DAN SANITASI DI PROVINSI NUSA TENGGARA TIMUR PADA MASA PANDEMI COVID-19 - Raissa Albezy Noreen (2023)
The issue of water and sanitation is a significant issue to be discussed, especially with the arrival of the COVID-19 virus which requires good water and sanitation to stop the spread of the virus. Even more so in East Nusa Tenggara Province which often experiences long dry seasons. Children are greatly affected by this problem, which in addition to threatening their health, also interferes with their development. In responding to this condition, the government is trying to make various efforts to be able to overcome this problem, one of which is the government cooperating with UNICEF. To be able to develop the analysis in this study, the concept of policy implementation for water and sanitation issues was used, especially in East Nusa Tenggara Province. This study uses a qualitative method with a descriptive research type. The final results of this study reveal that the cooperation established by the Indonesian government and UNICEF is carried out through the WASH Program by UNICEF and the implementation of the Country Program Action Plan (CPAP) policy involving several parties, one of which is the Ministry of National Development Planning/Bappenas to help overcome water and sanitation problems, especially happened in East Nusa Tenggara Province.